The Four–Seven Debate of Korean Neo-Confucianism and the Moral Psychological and Theistic Turn in Korean Philosophy - Bongrae Seok (Religions, 2018)
This paper discusses how Korean Neo-Confucian philosophers in the Joseon dynasty (1392⁻1910) explained the moral nature of the mind and its emotions. Among the philosophical debates of Korean Neo-Confucianism, the author of the paper focuses on the Four⁻Seven Debate (a philosophical debate about the moral psychological nature of the four moral emotions and the seven morally indiscrete emotions) to analyze its li⁻qi metaphysics (a philosophical explanation of the universe through the intricate and interactive relation between the two cosmic processes, li and qi) and its conflicting viewpoints on the moral psychological nature of emotion. Because of the ambiguities and inconsistencies in the Neo-Confucian explanation, specifically those of the Cheng⁻Zhu schools of Neo-Confucianism on the nature and functions of the mind, Korean Neo-Confucians struggled to bring Neo-Confucian li⁻qi metaphysics to the moral and practical issues of the human mind and moral cultivation. Later in the Joseon dynasty, some Korean Neo-Confucians discussed the fundamental limitations of li⁻qi metaphysics and developed their explanations for the goodness of the moral mind and the world from an alternative (i.e., theistic) viewpoint.